Pertimbangan Hakim dalam Menjatuhkan Putusan Denda Bersifat Minimum Khusus dalam Delik Narkotika - Heri Zuniarto (Lex Renaissance, 2020)
The eradication of criminal acts of narcotics has been carried out through a judicial process with the regulation of Law Number 35 of 2009 on Narcotics as a guideline for law enforcement. However, in practice, there are still problems, especially for judges in considering a fine sentence which is regulated specifically with a high enough limit. This study aims to determine the judges’ considerations in imposing a fair decision against a special minimum fine in narcotics crime. The research method used is normative-empirical based on statutory law material adjusted to the facts of its application in the judiciary, with juridical normative and empirical juridical approaches. The results of the research found that the special minimum provisions for fine sentences that were quite high were an obstacle for judges in considering the amount of fines to be imposed on the defendant, so that judges tended to impose the amount of fines according to the specific minimum limit of fines, although in implementing the verdict the convict preferred to serve imprisonment as an alternative to fines that cannot be paid. This phenomenon makes the application of fines in judges’ decisions inefficient, especially in the absence of regulations in the Narcotics Law regarding coercion in the context of the application of the penalty itself.